Orobanche lutea Baumg. (Orobanchaceae) in Poland: revised distribution, taxonomy, phytocoenological and host relations - Piwowarczyk, Renata; Krajewski, Łukasz (Biodiversity: Research and Conservation, 2015)
The paper presents current distribution of Orobanche lutea Baumg. in Poland based on a critical revision of herbarium and literature data as well as results of field investigations conducted between 1999-2014. Majority of localities are centred around the Silesia-Cracow, Małopolska and Lublin-Lviv Uplands. The greatest density of sites with probably the most abundant populations in Europe is in the central part of Silesia-Cracow Upland, which, by several hundred years, was heavily exploited for calamine mining (rich in zinc, lead and silver). This resulted in the formation of large areas of gangue containing toxic heavy metals. Since limestone, dolomite, marl and postglacial calcareous clay and sands occur there in most places, the soil is often strongly calcareous. Populations of O. lutea contain here many thousands of shoots. The distribution of the species in Poland is mapped. The taxonomy, biology, ecology and threats are also discussed.